(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Introduction. Quarantine is a complex definition that consists of administrative and sanitary measures designed to prevent the spread of communicable diseases to both humans and animals. Bans and restrictions that have been introduced, have significantly changed people’s lifestyles – individuals have become less physically active and were forced to spend most of their time at home. The aim of the study was to reveal the dominant factors contributing to students’ psycho-emotional health and physical activity during the quarantine period. Methods. This survey was conducted in April 2020 with 304 participating students. The anonymous survey collected demographic data and two standardized questionnaires were used: The International Physical Activity Questionnaire and General Health Questionnaire. Data were processed by SPSS Statistics 23 program. Results. Respondents’ level of physical activity during quarantine was as follows: high level – 42%, medium level – 41%; low level – 17 %. A negative correlation was found – with increasing physical activity, the sum of psycho-emotional state assessment score decreased (r = - .2702, p < .01), and with increasing age of respondents, their total level of physical activity also increased (r = .1364, p < .05). Conclusion. Low intensity of physical activity predominated at all levels of physical activity, for which the main reason was the remote learning during quarantine and recommendations to leave home only for essential matters. Regular physical activity and exercise may be a simple, inexpensive, and effective therapy during the quarantine, and physical activity is significant in treating student depression, stress, and/or increased anxiety. Keywords: depression, youth, stress, sedentary lifestyle.